Assess the Diagnostic Potential of Several Significant Biomarkers for Parkinson's Disease - Al-Bofkane, Khalid M. Khudhur; Hassin, Mohammed Bahry (American Journal of Biomedicine and Pharmacy, 2025)
Parkinson's disease (PD), a neurodegenerative disorder, is associated with altered blood biochemistry, this study investigates key biomarkers like dopamine, alpha-synuclein, Tau protein, TNF, beta-amyloid, IL-6, copper, and iron in both healthy individuals and PD patients, the study was conducted on (90) for both healthy and patients, both males and females were between the ages of 50 and 85 years old. The findings show that PD patients have significantly lower levels of dopamine (19.40 ± 0.82 pg/mL) than healthy people (31.58 ± 1.07 pg/mL, p < 0.01), which demonstrates its part in the disease's pathogenesis.; elevated levels of Tau protein (41.58 ± 2.97 ng/L vs. 9.85 ± 3.6 ng/L, p < 0.01) and alpha-synuclein (47.31 ± 1.91 pg/mL vs. 25.84 ± 2.07 pg/mL, p < 0.01) suggest neurodegenerative involvement; PD patients have higher levels of the markers of inflammation TNF and IL-6. further indicate neuroinflammation; and beta-amyloid levels are significantly higher in PD patients (168.78 ± 0.27 pg/mL) than in controls (80.65 ± 1.13 pg/mL, p < 0.01), highlighting the role of amyloid pathology in disease progression. A gender-based investigation showed only small variations, with females having slightly greater levels of alpha-synuclein and IL-6. The age-dependent character of PD-related biochemical alterations is further supported by age-stratified data in PD patients, which indicate gradual decreases in dopamine and iron along with rising levels of Tau protein and alpha-synuclein across age groups.